2017
DOI: 10.1177/0954409717693147
|View full text |Cite
|
Sign up to set email alerts
|

Moving element analysis of discretely supported high-speed rail systems

Abstract: In this paper, a computational scheme in conjunction with the moving element method has been proposed to investigate the dynamic response of a high-speed rail system in which the discrete sleepers on the subgrade support the railway track. The track foundation is modeled as a beam supported by uniformly spaced discrete spring-damper units. The highspeed train is modeled as a moving sprung-mass system that travels over the track. The effect of the stiffness of the discrete supports, train speed, and railhead ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…where p 1 � 1.431 and p 2 � − 0.0423, and R 2 is calculated to be 0.9896. According to equation (32) and as long as the objective d 2 is satisfied, the objective d 3 can also be satisfied. erefore, the optimization objective of the horizontal vibration reduction of a KLK2 high-speed elevator equates to d 1 and d 2 . erefore, the model of the optimization objective of the Shock and Vibration horizontal vibration reduction of a KLK2 high-speed elevator expressed by equation (31) was modified to…”
Section: Optimization Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where p 1 � 1.431 and p 2 � − 0.0423, and R 2 is calculated to be 0.9896. According to equation (32) and as long as the objective d 2 is satisfied, the objective d 3 can also be satisfied. erefore, the optimization objective of the horizontal vibration reduction of a KLK2 high-speed elevator equates to d 1 and d 2 . erefore, the model of the optimization objective of the Shock and Vibration horizontal vibration reduction of a KLK2 high-speed elevator expressed by equation (31) was modified to…”
Section: Optimization Correlation Analysismentioning
confidence: 99%
“…Dai et al [30] proposed the moving element method which was found to have advantages over the other numerical methods for solving high-speed dynamic response problems. In conjunction with the moving element method, a three-phase computational scheme was proposed to account for the motion of the unsupported sleepers in relation to the truncated rail segment in the moving coordinate system, and the study found that a high-speed train that travels over a discretely supported track produced more severe vibrations than that which travels over a continuously supported track of equivalent foundation stiffness [31,32]. e vibration suppression of the high-speed elevator is often achieved by developing and installing vibration dampers.…”
Section: Introductionmentioning
confidence: 99%
“…Using the moving Green function, Sheng et al 4 dealt with interactions between wheels and a track with or without rail dampers. Through moving element method, Dai et al 5 studied a high-speed track system that was discretely supported. To understand the vehicle-structure interaction, the direct method was used to formulate governing equilibrium equations and impose constraint equations.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the wheel sliding, initial train deceleration, initial train speed, and the severity of the railhead roughness on the dynamic response of the HSR were investigated. Dai et al (2017) proposed a computational scheme in conjunction with the MEM to investigate the dynamic response of a high-speed train-track system in which the discrete sleepers on the sub-grade support the railway track.…”
Section: Introductionmentioning
confidence: 99%